Effect of exogenous flavonoids on nodulation of pea (Pisum sativum L.) - Novák, K; Chovanec, P; Skrdleta, V; Kropácová, Martina; Lisá, Ludmila; Nemcová, Marie (Journal of experimental botany, 2002)
Selected flavonoids that are known as inducers and a suppressor of nodulation (nod) genes of the symbiotic bacterium Rhizobium leguminosarum bv. viciae were tested for their effect on symbiosis formation with garden pea as the host. A solid substrate was omitted from the hydroponic growing system in order to prevent losses of flavonoids due to adsorption and degradation. The presumed interaction of the tested flavonoids with nod genes has been verified for the genetic background of strain 128C30. A stimulatory effect of a nod gene inducer naringenin on symbiotic nodule number formed per plant 14 d after inoculation was detected at concentrations of 0.1 and 1 micro g ml(-1) nutrient solution. At 10 micro g ml(-1), the highest concentration tested, naringenin was already inhibitory. By contrast, nodulation was negatively affected by a nod gene suppressor, quercetin, at concentrations above 1 micro g ml(-1), as well as by another tested nod gene inducer, hesperetin. The deleterious effect of hesperetin might be due to its toxicity or to the toxicity of its degradation product(s) as indicated by the inhibition of root growth. Both the stimulatory effect of naringenin and the inhibitory effect of quercetin on nodule number were more pronounced at earlier stages of nodule development as revealed with specific staining of initial nodules. The lessening of the flavonoid impact during nodule development was ascribed to the plant autoregulatory mechanisms. Feedback regulation of nodule metabolism might also be responsible for the fact that the naringenin-conditioned increase in nodule number was not accompanied by any increase in nitrogenase activity. By contrast, the inhibitory action of quercetin and hesperetin on nodule number was associated with decreases in total nitrogenase activity. Naringenin also stimulated root hair curling (RHC) as one of the earliest nodulation responses at concentrations of 1 and 10 microg ml(-1), however, the same effect was exerted by the nod gene suppressor, quercetin, suggesting that feedback regulatory mechanisms control RHC in the range of nodulation-inhibiting high flavonoid concentrations. The comparison of the effect of the tested flavonoids in planta with nod gene activity response showed a two orders of magnitude shift to higher concentrations. This shift is explained by the absorption and degradation of flavonoids by both the symbionts during 3 d intervals between hydroponic solution changes. The losses were 99, 96.4, and 90% of the initial concentration of 10 micro g ml(-1) for naringenin, hesperetin, and quercetin, respectively.
Keywords: flavonoidy; Flavanones; Flavonoids; hesperidin; beta-Galactosidase; beta-galaktosidasa; quercetin; symbióza; Hydroponics; Symbiosis; hydroponie; hrách setý; kořeny rostlin; Pisum sativum; nitrogenasa; Hesperidin; flavanony; Rhizobium leguminosarum; Plant Roots; Nitrogenase; Quercetin